Effects of fecal stream deprivation on human intestinal barrier after loop ileostomy. Issue 6 (26th April 2022) - Li, Xiaolong; Ma, Haitao; Sun, Yiming; Li, Teming; Wang, Cheng; Zheng, Hong; Chen, Guoqing; Du, Guangsheng; Ji, Guangyan; Yang, Hua; Xiao, Weidong; Qiu, Yuan
Abstract: Background and Aim: Intestinal homeostasis is closely associated with the normal intestinal luminal physiological environment. Temporary loop ileostomy changes the intestinal structure and diverts the fecal stream, thereby disturbing the intestinal environment. This study aimed to clarify the changing situation of the human intestinal mucosa barrier in the absence of a fecal stream after loop ileostomy. Methods: We obtained paired samples from the fed (fecal stream maintained) and unfed (no fecal stream) portions of the loop ileostomy and subjected these samples to RNA sequencing. We also determined transepithelial electrical resistance. The mucus layer thickness and content of MUC2, tight junction proteins, and common antimicrobial peptides in ileum mucosa were studied. Results: Transcriptome data revealed that genes associated with enhancing the intestinal barrier function of the unfed ileum were significantly decreased and genes associated with immune defense response were significantly increased. The transepithelial electrical resistance was lower and the mucus layer thickness was thinner in the unfed ileal mucosa than in the fed ileum. The MUC2, Occludin, and zonula occludens 1 content was lower in the unfed ileum than in the fed ileum. α‐Defensin 5, α‐defensin 6, and lysozyme content was higher in the unfed ileum than in the enterally fed ileum. Conclusion: Intestinal barrier function is weakened after long‐term fecal diversion, but antimicrobiota defense function is strengthened. Thus, the intestinal mucosa barrier adopts an alternative stable state during fecal diversion, which may explain the clinical paucity of cases of enterogenic infection caused by loop ileostomy.